SOSIALISASI TANAMAN BERKHASIAT SEBAGAI PELANCAR ASI (AIR SUSU IBU) DI KECAMATAN ARJASA SITUBONDO - Diana Lady Yunita Handoyo; Sri Nur Atiqah; Nur Diana Kholidah; Mutmainnatus Solihah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The use of efficacious plants as breast milk has been known for a long time by the people of Arjasa District Situbondo Regency The use of these plants has been used for a long time and passed down from generation to generation. However, with the passage of time, public knowledge related to the efficacy of plants as breast milk carriers has begun to become scarce and is only known by a certain group of people. The purpose of this community service activity (PKM) is to socialize to the community about plants that can be used as breast milk carriers based on the results of previous ethnobotany studies. PKM activities carried out in the form of socialization to breastfeeding mothers and productive mothers as many as 20 people. The results of the PKM stated that 100% of the socialization participants stated that this activity was very beneficial to the participants, especially in terms of knowledge about the use of herbal plants as breast milk promoters